Power Quality Concerns due to Power System Improvements with Renewable Energy Sources and its Remedies - Thiruburasundari, V.; Ramya, G.; Ramadevi, N.; M, Pameela (Journal of Trends in Computer Science and Smart Technology, 2023)
Power quality issues are becoming increasingly important due to the rapid changes in energy network infrastructure caused by technological advancements in distributed generation. Distributed generation involves the use of small-scale, decentralized power sources that can be located close to the end-users, and can include solar panels, wind turbines, and fuel cells. While distributed generation can help to reduce greenhouse gas emissions and increase energy efficiency, it can also create new challenges for the power grid, particularly in terms of power quality. To address these power quality issues, numerous solutions are available at present. One approach is to use advanced control systems that can monitor and manage the voltage and frequency of the power grid in real-time. This can involve using smart inverters that can adjust the power output of distributed generation sources to maintain a stable voltage supply. Other solutions involve the use of energy storage systems, such as batteries or flywheels, which can help to smooth out fluctuations in power output from distributed generation sources. Another approach is to improve the design and operation of the power grid itself. This can involve the use of new transmission and distribution techniques, such as the deployment of microgrids or the integration of energy storage systems into the power grid. Additionally, advances in power electronics and communication technologies can be used to improve the reliability and the efficiency of the power grid.
Keywords: Power quality problems; Power quality solution; renewable energy sources; power grid